A DSP-based DS-CDMA multiuser receiver employing partial parallel interference cancellation. - Correal, N.S.
The implementation of advanced DS-CDMA receivers based on multiuser detection principles is becoming a reality thanks to the combination of an improved understanding of the theoretical basis of multiuser detection and advances in digital, mixed-signal, and RF technologies. Due to their lower complexity, subtractive interference cancellation approaches are attractive for the practical implementation of multiuser detection. In a parallel interference cancellation receiver, it is practical to use the soft outputs of a matched filter bank for amplitude estimation. A bias arises in the decision statistics, however, due to imperfect estimation and interference cancellation. In this paper, the source of the bias is explicitly recognized, and a partial interference cancellation scheme that mitigates the negative effects of biased estimation and significantly improves system performance is proposed. A practical real-time algorithm that significantly reduces the implementation complexity of this scheme without sacrificing performance is then derived. To facilitate a software radio implementation, the signal processing complexity of the approach is characterized. The real-time processing algorithm is tested via implementation in software on a floating-point general-purpose DSP. The prototype includes a flexible software-based architecture which performs IF sampling and uses digital downconversion prior to baseband processing. The hardware test setup is described, and the results are presented and compared with simulation and analytical results. The experimental results confirm the simulation and analytical results which show large performance gains over the conventional matched filter
Keywords: AWGN channels; DSP-based DS-CDMA multiuser receiver; IF sampling; RF technology; Amplitude estimation; Analytical results; Baseband processing; Bias source; Biased estimation; Decision statistics; Digital downconversion; Digital technology; Floating-point general-purpose DSP; Hardware test setup; Imperfect estimation; Implementation complexity reduction; Matched filter bank; Mixed-signal technology; Multiuser detection; Parallel interference cancellation receiver; Partial parallel interference cancellation; Real-time processing algorithm; Signal processing complexity; Simulation results; Soft outputs; Software radio implementation; Software-based architecture; Subtractive interference cancellation; System performance